The Impact of Board Gender Diversity on Bank Credit Risk - Setiawan, Rahmat; Khoirotunnisa, Fani (The International Journal of Business Review (The Jobs Review), 2020)
Abstract. Credit risk is the most important risk to consider because it is the biggest risk faced by banks. To control these risks, banks make various efforts such as implementing good corporate governance. One of the GCG strategies undertaken by banks is to diversify the company's board members. This research aims to examine the effect of board gender diversity on credit risk. The sample was determined using purposive sampling with data analysis techniques using linear regression. Research data using Stata 14. Using a sample of 41 Indonesian banks over a period from 2012 to 2018, this research finds that board gender diversity has a significant negative effect on bank credit risk. This study concludes that the greater the proportion of women on the bank's board, the less credit risk the bank has.